Study on the assessment of disease severity in COVID-19 patients from D-dimer estimation in a tertiary care level hospital, in West Bengal - Bhaduri Bhattacharyya, Nandini; Bardhan, Jayati (Asian Journal of Medical Sciences, 2023)
Background: Coronavirus disease 2019 (COVID-19) is a RNA virus which infects both human beings and animals. COVID-19 infection is presently a very important, global health related problem. It is contagious. The COVID-19 or severe acute respiratory syndrome (SARS)-CoV-2 virus affects the lungs very commonly through the angiotensin converting enzyme 2 receptor which is present in abundance on the surface of type II alveolar cells. It leads to SARS. The severely ill COVID-19 patients suffer from massive intra vascular clot formation. Therefore, coagulation tests are very useful to assess the severity of the cases. Aims and Objectives: The aim of our study is to assess, that whether by examining the blood of a COVID-19 patient for D-Dimer, the treating physician can judge the severity of the case and come to a conclusion regarding the line of management. Materials and Methods: This is a retrospective study conducted in the departments of Pathology and Radiology of RG Kar Medical College. Records of the patients who were admitted for COVID-19, from September 2020 to September 2021, have been studied for their D dimer levels. The computed tomography (CT) scan findings of the respective patients have also been studied from the departmental records. Results: In our study, the median value of D-Dimers of 80 samples came out to be 1.4. (1) CT scores, (2) presence or absence of crazy paving sign, and (3) perilobular fibrosis in CT scan have been studied and compared with the median D Dimer values. It has been seen from our study that out of 54 cases whose D-Dimers were <1.4, 41 cases had moderate CT score, and 13 had CT score in the severe range, 26 cases had crazy paving sign in their CT findings, and 28 cases did not show crazy paving sign in their CT findings, and 22 cases had perilobular fibrosis in their CT reports, and 32 cases did not have perilobular fibrosis. The P-values came out to be <0.05 for all the three parameters. Conclusion: We concluded from the study that D-Dimer levels can reflect the severity of lung parenchymal injury and can be used to judge the severity and to plan the line of management of COVID cases.